“Whatever Did Ever Happen to the Likely Lads”? Social Change, Mobility, Class, and Identity in the UK 1969–2019. - Warren, Jon (Frontiers in Sociology, 2020)
This paper reflects upon issues of class and identity in the UK over the last 50 years. 1969 is a useful starting point, economically and technologically it can be regarded as the high tide of the vision of a Britain remade in what the then Prime Minister Harold Wilson had termed “the white heat of technology”. That technology had produced Concord the world’s first supersonic airliner which made its debut that year. This successful Anglo French collaboration also showed how Britain was rapidly moving into a different relationship with Europe a process that culminated in the UK’s entry into the EEC or the “common market” as it was more usually referred to on January 1st 1973. Sociologically, it marked the publication of Goldthorpe et al Affluent worker studies (1968 & 1969), which examined the idea that increasing affluence was breaking down established class structures, roles and attitudes. This debate about whether the changing nature of work brought with it a fundamental change in class structure and identity has been going on ever since.